Changes in the incidence of acute gonococcal and nongonococcal salpingitis. A five-year study from an urban area of central Sweden. Issue 4 (August 1978) - Forslin, L; Falk, V; Danielsson, D
Abstract : The incidence of acute gonococcal and nongonococcal salpingitis for a five-year-period (1970–74) was studied retrospectively in an urban area of central Sweden. The investigation was undertaken to see if the reported decrease of gonorrhoea in Sweden had been followed by a change in the incidence of gonococcal salpingitis–the most common complication of gonorrhoea. The study showed that the relative incidence of acute gonococcal salpingitis had decreased even more than urogenital gonorrhoea and these findings thus indicate a real decrease of gonorrhoea. At the same time there were more patients with nongonococcal salpingitis. During the period of the study the gonococcal complement-fixation test (GCFT) gave positive results in 40% to 80% of the patients with gonococcal salpingitis. The yield with this test was only 4% in patients with nongonococcal salpingitis during 1970 but it increased successively and was 23% in 1974. This increase was statistically highly significant (P less than 0.001).